Variability of surface mass balance in the Mizuho Plateau, Antarctica - Satow, Kazuhide (1985)
P(論文) On the basis of the data of surface mass balance along the traverse routes in 1968-1983,mean and variation of the annual balance were obtained in the Mizuho Plateau, Antarctica. A year-to-year variation of the surface mass balance showed a general increase during the period of the measurement. The climatic effect and the effect of surface microrelief, such as sastrugi and dunes, on the mass balance variability were assessed. The former prevailed in a high accumulation zone of the coastal region, and the latter became larger inland. departmental bulletin paper